2016
DOI: 10.1039/c6cp03637f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ultrathin V-oxide layers on Rh(111) in catalytic oxidation of ammonia and CO

Abstract: Catalytic oxidation of ammonia and CO has been studied in the 10 À4 mbar range using a catalyst prepared by depositing ultra-thin vanadium oxide layers on Rh (111)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
(74 reference statements)
2
24
0
Order By: Relevance
“…In catalytic methanol oxidation the system VO x /Rh(111) exhibited a high catalytic activity and displayed remarkable dynamic behavior [25,31], whereas VO x /Pt(111) showed negligible catalytic activity and practically no dynamics at all. In this comparison we refer to submonolayer coverages of VO x and reaction conditions in the 10 −4 mbar range.…”
Section: Catalytic Activity Of Vo X /Pt(111)mentioning
confidence: 99%
See 1 more Smart Citation
“…In catalytic methanol oxidation the system VO x /Rh(111) exhibited a high catalytic activity and displayed remarkable dynamic behavior [25,31], whereas VO x /Pt(111) showed negligible catalytic activity and practically no dynamics at all. In this comparison we refer to submonolayer coverages of VO x and reaction conditions in the 10 −4 mbar range.…”
Section: Catalytic Activity Of Vo X /Pt(111)mentioning
confidence: 99%
“…A natural question was how general the phenomenon of a reaction-induced island coalescence is, i.e., whether such ripening processes can also be observed in other reactions [27], with different support materials [28][29][30], and with other oxidic catalysts. It turned out that a number of oxidation reactions showed qualitatively the same behavior on VO x /Rh(111) as long as O 2 is used as oxidizing agent [31].…”
Section: Introductionmentioning
confidence: 96%
“…One of the first questions that were asked after catalytic methanol oxidation exhibited quite remarkable reaction dynamics on VO x /Rh(111), was how general the island coalescence mechanism is. Experiments in which methanol oxidation was replaced by the H 2 + O 2 reaction, the NH 3 + O 2 reaction, and catalytic CO oxidation on VO x /Rh(111) showed in fact qualitatively the same behavior as in catalytic methanol oxidation (von Boehn et al, 2016). However, all these reactions have in common that O 2 is used as oxidizing agent.…”
Section: Oxidation With Nomentioning
confidence: 76%
“…What does not fit into the concept of reactive phase separation in the present case is that the coarsening does not approach a finite value. A control experiment in which V-oxide on Rh(111) was annealed in O 2 only, revealed that also in this case VO x islands of macroscopic size are formed (von Boehn et al, 2016). The condensation of VO x into stripes and circular islands under reaction conditions therefore appears to be driven by thermodynamics.…”
Section: Choice Of Model System and Methods Of Investigationmentioning
confidence: 93%
See 1 more Smart Citation